SOSIALISASI KONSEP SANITASI LINGKUNGAN PERMUKIMAN PESISIR (UNIVERSITAS KHAIRUN, 2023)
ABSTRACTCoastal settlements have unique and distinctive characteristics, but behind that save quite serious environmental problems when the residents do not care about environmental sanitation problems. This happened in coastal settlements in Tadenas Village, Pulau Moti District. Even though at this time the sanitation conditions have not shown any visible damage to the water bodies, in the future this residential area will be prepared as a tourist village, so that currently care for the marine environment needs to be maintained. Referring to the SDGs in supporting and strengthening local community participation in improving water and sanitation management, strengthening community participation is very much needed in handling environmental sanitation problems. The importance of education for residents and community-based participatory mapping for an inventory of environmental sanitation conditions, because the community is the main stakeholder who knows and understands the characteristics of the physical condition of the environment they live in. The purpose of Community Service activities is to provide knowledge about environmentally sound sanitation and to map out environmental sanitation conditions by involving community participation in order to get an overview of the characteristics of sanitation in settlements on the water so that it can become a planning database for efforts to handle sustainable sanitation.Â Keywords: environment sanitation, coastal settlement, SDGs.